Efficacy of Two Probiotic Products Fed Daily to Reduce Clostridium perfringens-Based Adverse Health and Performance Effects in Dairy Calves - Charley Cull; Vijay K. Singu; Brooke J. Cull; Kelly F. Lechtenberg; Raghavendra G. Amachawadi; Jennifer S. Schutz; Keith A. Bryan (MDPI AG, 2022)
Clostridium perfringens is a spore-forming, anaerobic bacterium which produces toxins and exoenzymes that cause disease in calves, especially necro-hemorrhagic enteritis-associated diarrhea often resulting in death. Clostridium infections are currently being treated with antibiotics, but even with the prudent administration of antibiotics, there are significant rates of recurrence. Probiotics, an alternative to antibiotics, are commonly employed to prevent clostridial infections. The objectives of our study were to demonstrate that two commercially available products, when used as daily, direct-fed microbials, are effective in reducing adverse effects of an experimentally induced C. perfringens infection in dairy calves. We conducted a single site efficacy study with masking using a randomized design comprising 10 calves allocated to 3 treatment groups (probiotic 1, probiotic 2, and control). The procedures such as general health scores, body weight, blood samples, and fecal sample collections were done followed by experimental challenge of calves with C. perfringens. Daily feeding of L. animalis LA51 and P. freudenreichii PF24 without or with Bacillus lichenformis CH200 and Bacillus subtilis CH201, before, during and after an oral challenge of C. perfringens significantly reduced the incidence and severity of diarrhea while improving general impression and appearance scores of calves. Most notably, survival of calves in the two probiotic-fed groups was significantly higher than for control calves and further substantiates the potential economic and health benefits of feeding effective probiotics.